2016
DOI: 10.1007/s11356-016-7673-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pesticide and phthalate residues in tea by QuEChERS method and their fate in processing

Abstract: In this study, the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method was applied for the analysis of the multiclass pesticide residues of 12 organochlorines (OCs), 9 organophosphates (OPs), 11 synthetic pyrethroids (SPs), 4 herbicides, 6 phthalates in raw tea (loose tea, branded tea and herbal tea), and tea infusion in 4 different containers (glass cup, earthen cup, plastic bag and disposal cup). In loose tea and branded tea residues, malathion (0.257 and 0.118 mg kg), cypermethrin (0.065 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…It has attracted comprehensive attention worldwide owing to its anti-oxidation, anti-hyperglycemia, anti-cardiovascular, anti-bacterial, anti-obesity, and health care functions. , However, organic contaminants, heavy metals, and pesticide residues in teas are important factors adversely affecting tea quality and safety, which has become an urgent concern. In recent years, domestic and foreign researchers have confirmed that the detectable rate of PAEs contamination in tea is as high as 100%, with DMP, DEP, di-isobutyl phthalate (DiBP), DBP, and DEHP being the most commonly detected in tea. , A method for detecting PAEs in tea and tea infusion has been established. , By means of these methods, researchers found that PAEs are highly accumulated in tea mature leaves. Fortunately, tea processing can facilitate PAEs degradation, in which the drying process was found to be the main stage for PAEs release during green tea and black tea processing. , …”
Section: Introductionmentioning
confidence: 99%
“…It has attracted comprehensive attention worldwide owing to its anti-oxidation, anti-hyperglycemia, anti-cardiovascular, anti-bacterial, anti-obesity, and health care functions. , However, organic contaminants, heavy metals, and pesticide residues in teas are important factors adversely affecting tea quality and safety, which has become an urgent concern. In recent years, domestic and foreign researchers have confirmed that the detectable rate of PAEs contamination in tea is as high as 100%, with DMP, DEP, di-isobutyl phthalate (DiBP), DBP, and DEHP being the most commonly detected in tea. , A method for detecting PAEs in tea and tea infusion has been established. , By means of these methods, researchers found that PAEs are highly accumulated in tea mature leaves. Fortunately, tea processing can facilitate PAEs degradation, in which the drying process was found to be the main stage for PAEs release during green tea and black tea processing. , …”
Section: Introductionmentioning
confidence: 99%
“…Excessive levels of pesticide residues, such as organophosphorus chemicals, organochlorines, carbamates, pyrethroids, herbicides, and neonicotinoids, are a serious safety issue that has been monitored for many decades and aroused increasing attention [216,219,228,229]. Specifically, chlorpyrifos, bifenthrin, lambda-cyhalothrin, cypermethrin, imidacloprid, and acetamiprid were frequently detected pesticides in tea [215,218].…”
Section: Potential Safety Issuesmentioning
confidence: 99%
“…Even the banished organochlorine pesticide residues were found in these products [5][6][7]. Also, organophosphorus pesticides were found in herbs commercialized in China [8,9], India [10,11], Italy [12], and Iran [13]. Some studies also detected pyrethroids in herbs from India [10,11], Italy [12], and China [14].…”
Section: Introductionmentioning
confidence: 99%
“…Also, organophosphorus pesticides were found in herbs commercialized in China [8,9], India [10,11], Italy [12], and Iran [13]. Some studies also detected pyrethroids in herbs from India [10,11], Italy [12], and China [14]. Few studies have been carried out aiming at the determination of pesticides in herbs consumed in Brazil, and only a restricted number of herbs and analytes Article Related Abbreviations: ACN, acetonitrile; GCB, graphite carbon black; GC-MS, gas chromatography -mass spectrometry; ISTD, internal standard; MRLs, maximum residue limits; QuEChERS, quick, easy, cheap, effective, rugged, and safe procedure; DLLME, dispersive liquid-liquid microextraction; PSA, primary secondary amine; SAX, strong anion exchange; TPP, triphenyl phosphate.…”
Section: Introductionmentioning
confidence: 99%